Urban Economic Growth in the Chinese Heterogeneity Space - Izotov, Dmitry Aleksandrovich (Economy of Regions, 2017)
The purpose of the study is to assess the factors of urban economic growth in Peoples Republic of China (PRC) in the framework of heterogeneous space, meaning as the regional diversity of economic systems, in the context of the current period of market reforms. The article shows that urban development is a way to achieve a sustainable rate of Chinas high economic growth. The author presents the description of the model and spatial characteristics of economic growth & urbanization in China. Using numerous statistical sources, the author has revealed that the high values of Chinas economic growth were observed in the conditions of high urbanization rates & low per capita income. I have estimated the factors of urban economic growth in the framework of PRC's heterogeneous space based on the neoclassical approach. In accordance with the assessment, the author found that spatial heterogeneity has a significant impact on the differences in the ratio of the factors of economic growth in Chinese cities. The contribution of extensive factors continues to play a key role in Chinas urban economic growth, with the highest proportion of capital input for coastal cities & towns, and labour input - for interior regions urban areas. As the assessment showed, intensive factors have a visible impact on economic growth only for coastal cities & towns. The author suggests that the economic growth in China is generated mainly coastal cities & towns, and investments in the interior regions urban areas only maintain the required employment growth for ensuring social stability. For this reason, the Russian economy needs the extension of relations with agglomerations placed in seaside regions of China as well as the development of innovative and technological joint projects.